Perancangan Website Sistem Informasi KONI Menggunakan Metode Design Thinking - Ebimbi, Selgi Agilsa; Anwar, Sariyun Naja; R Soelistijadi (STMIK Budi Darma, 2024)
KONI Kendal Regency is an achievement sports organization in the Kendal Regency area which has various activities and achievements from athletes to be informed to the general public through a platform that can be accessed by many people. However, so far the Kendal Regency KONI administrators still use manual data and information recording so this is less effective and efficient. Therefore, this research provides a solution, namely a website-based information system as a promotional tool for organizations with the community. The process of developing the Kendal Regency KONI information system website uses the Design Thinking method to determine solutions to existing problems. The Design Thinking method is a problem solving method that focuses on the user. There are five stages that must be carried out in the Design Thinking method, namely empathize, define, ideate, prototype and test. This research resulted in a prototype design for the KONI Information System for Kendal Regency. Based on usability testing using the System Usability Scale (SUS) calculation, the final SUS score was 75 with a Grade Scale of